Towards sustainable tourism: a case study of Lijiang, China - Zhao, Ge (Kansas State University, 2010)
With the economic growth in the last three decades, tourism is becoming bigger business than ever before in China. One of the most popular tourism destinations in China is ancient towns. While the tourism industry encourages economic growth in ancient towns, it brings negative side-effects as well. The purpose of this report is to detect the economic and social sustainability of the tourism industry in Chinese ancient towns, taking Lijiang, Yunnan Province as an example. The report also provides responsive suggestions for the tourism industry in Lijiang in the end. To measure the sustainability of tourism in Lijiang, the report employs a total of 33 indicators in social, cultural, economic and political dimensions and a five-point evaluation system to convert different indicators into a relatively consistent measurable scale. The outcome of the analysis indicates that: 1) tourism in Lijiang is unsustainable in social dimension because of the paramount pressure on land use and the traditional life style caused by overhaul tourist population poured into Lijiang in recent years; 2) tourism in Lijiang has generally played a positive role in local culture’s preservation; 3) the fast-growing economy brought by tourism in Lijiang is potentially unsustainable because of the imbalanced benefit distributions; 4) tourism in Lijiang is almost totally government-oriented and lacks a certain opportunities for public participation. The findings in each aspect of the tourism industry in Lijiang help decision makers understand both strengths and weaknesses of tourism in Lijiang better to make responsive policies and strategies to ensure a more sustainable future.
Keywords: Sustainable Tourism; Lijiang; Ancient Towns; Geography (0366); Urban and Regional Planning (0999)